Clinical Features in Children With Kawasaki Disease Shock Syndrome: A Systematic Review and Meta-Analysis - Zheng, Zhimin; Huang, Yanzhi; Wang, Zhiyi; Tang, Jia; Chen, Xiaoqian; Li, Ying; Li, Meng; Zang, Chengye; Wang, Yibo; Wang, Liwu; Ma, Yingwei; Sun, Liwei (Frontiers in Cardiovascular Medicine, 2021)
Objective This study aimed to identify the clinical features of Kawasaki disease shock syndrome (KDSS) in children. Methods Case-control studies of KDSS and KD children up until April 30, 2021 were searched in multiple databases. Qualified researches were retrieved by manually reviewing the references. Review Manager 5.3 was used for statistical analysis. Results The results showed that there was no significant difference in the incidence of male and female in children with KDSS. Children with KDSS compared with non-shocked KD, there were significant difference in age, duration of fever, white blood cell count, percentage of neutrophils, platelet count C-reactive protein level, alanine transaminase concentration, aspartate transaminase concentration, albumin concentration, sodium concentration, ejection fraction and length of hospitalisation as well as the incidence of coronary artery dilation, coronary artery aneurysm, left ventricular dysfunction, mitral regurgitation, pericardial effusion, initial diagnosis of KD, IVIG resistance and receiving second dose of IVIG, vasoactive dugs, hormones, albumin. In contrast, there was no difference in the hemoglobin concentration, erythrocyte sedimentation rate and the incidence of conjunctival injection, oropharyngeal change, polymorphous rash, extremity change, incomplete KD. Conclusion Current evidence suggested that children with KDSS had more severe indicators of inflammation and more cardiac abnormalities. These patients were resistant to immunoglobulin treatment and required extra anti-inflammatory treatment.